Potential determinants of vaccine hesitancy among celiac disease patients: a single cohort analysis - Rehman, Shazia; Rehman, Erum; Holy, Ondrej (Frontiers in Public Health, 2023)
Introduction Though researchers and scholars have greatly emphasized addressing the influencing factors of vaccination hesitancy, little attention has been paid to patients with celiac disease. Addressing the variables hampering attitudes might help direct appropriate patient advocacy and doctor-patient communication endeavors to encourage vaccination among celiac disease patients. The present investigation seeks to explore the coverage against vaccine-preventable diseases, vaccination attitudes, and related possible factors among celiac disease patients in the Pakistani setting. Methods A self-reported online survey was conducted in Islamabad, Pakistan, for celiac disease patients aged 18 and above. The questionnaire was completed by 226 participants, with a response rate of 43.8%. The influencing variables for vaccination hesitancy were examined, and 95% confidence intervals for the crude and adjusted odds ratios were computed. Results Among the study population, the majority were females, with a ratio of 75.66%. A prominent proportion of 69.03% was observed for influenza vaccination, while 39.82% were unable to recall all of the vaccinations they had previously received. Only 7% of the patients were considered to have a negative attitude toward vaccination, compared to an estimated 76% who were in favor of it. The significantly positive influencing factors observed toward vaccination were being well-educated (graduate, master, or above), possible recurrence of vaccine-preventable diseases with declining vaccination coverage (adjusted OR: 13.36), and increased confidence in vaccines from health care experts compared to electronic media (adjusted OR: 8.41). Contrarily, practicing complementary and alternative medicines (adjusted OR: 5.59), willingness to get vaccinated again in the future (adjusted OR: 15.59), and prior negative perspectives (adjusted OR: 1.01) were the determinants with a significant negative association. Discussion In conclusion, the outcomes of the current work raise the possibility that health practitioners may be accountable for inappropriately prescribing vaccines to this demographic since 77% of the participants had a favorable attitude toward vaccination. These findings could serve as a springboard for creating targeted immunization efforts to raise vaccination coverage against vaccine-preventive diseases among celiac disease patients.